Ag–CoO nanocomposites for gas-phase oxidation of alcohols to aldehydes and ketones: intensified O2 activation at Ag–CoO interfacial sites. Issue 24 (7th November 2020) - Liu, Kun; Zhao, Yichen; Wang, Jiale; Xue, Qingsong; Zhao, Guofeng
Abstract : The fabrication of qualified catalysts is a key issue to implement gas-phase aerobic alcohol oxidation, but necessarily requires understanding the structures of catalytic active sites and the supply of active oxygen species. Abstract : The fabrication of qualified catalysts is a key issue to implement gas-phase aerobic alcohol oxidation but necessarily requires understanding the structures of catalytic active sites and the supply of active oxygen species. Herein, we present one example of the Ag–CoO/Ti- powder catalyst for gas-phase benzyl alcohol aerobic oxidation. The first interesting observation is that the Ag–Co3 O4 ensembles on the fresh catalyst could be transformed into Ag–CoO due to the presence of reductive benzyl alcohol. The preferred catalyst with 3 wt% Ag and 3 wt% CoO exhibits 93% benzyl alcohol conversion and 99% benzaldehyde selectivity at a weight hourly space velocity of 20 h −1 and a temperature of 240 °C. The structures of Ag–CoO ensembles and oxygen species supply were probed and identified by electron microscopy and other spectroscopy techniques in combination with temperature-programmed thermal analyses, pulse experiments, and kinetic studies. In nature, the oxygen species is generated at the Ag–CoO interfacial sites in the form of atomic oxygen with appropriate chemisorption strength on these sites to achieve a high oxidation activity of benzyl alcohol. Moreover, the Co3 O4 ↔ CoO cycle is promoted by Ag at low temperature such as 240 °C to endow the Ag–CoO ensembles with excellent catalytic performance.